Efeitos da modulação do córtex pré-frontal dorsolateral induzida pela estimulação transcraniana por corrente contínua (ETCC) na dependência do álcool - Silva, Morgana Croce da (2013)
Neuromodulation by transcranial Direct Current Stimulation (tDCS) has been shown to reduce acute substance craving in drug addicts, and improve cognition in patients suffering from neuropsychiatric diseases via its modulating effects on cortical excitability, and activity. Here we aimed to explore if tDCS is suited to reduce relapse probability over a prolonged time course, and improve cognitive processes in alcoholism, which is often accompanied by frontal executive dysfunctions. We examined the effects of repeated anodal tDCS (2 mA, 35 cm2, 20 minutes) over the left dorsolateral prefrontal cortex (DLPFC) on relapse to the use of alcohol in addicted subjects from outpatient services, who received additional routine clinical treatment. Furthermore, event related potentials (ERPs), cognitive and frontal executive processes, depressive and anxiety symptoms were obtained before and after treatment. From thirteen alcoholic subjects, seven were randomized to sham-tDCS and six to real tDCS treatment (once a week for five consecutive weeks). Four alcoholic subjects from the tDCS group and one in the sham-tDCS group relapsed. Changes of ERP-evoked current densities in the prefrontal cortex (PFC) were large in the sham-tDCS group (most of the patients kept abstinent) and were much smaller in tDCS group (most of the patients relapsed), but improvement of executive functions tended to be larger and reduction of craving and depressive symptoms were significantly larger in the tDCS group compared to the shamtDCS group. We conclude that repeated anodal tDCS over the left DLPFC may improve executive functions and reduce craving and depressive symptoms in alcoholics, but at the expense of a larger proportion of relapses. A different montage of tDCS electrodes need to be investigated for more favorable clinical and cognitive outcomes in the treatment of alcoholism.